Successful treatment with cladribine of Erdheim-Chester disease with orbital and central nervous system involvement developing after treatment of Langerhans cell histiocytosis - Perić, Predrag; Antić, Branislav; Knezević-Ušaj, Slavica; Radić-Tasić, Olga; Radovinović-Tasić, Sanja; Vasić-Vilić, Jasenka; Sekulović, Leposava; Tarabar, Olivera; Tukić, Ljiljana; Jovandić, Stevo; Magić, Zvonko (Vojnosanitetski pregled, 2017)
Introduction. Erdheim-Chester disease (ECD) is a rare, systemic form of non-Langerhans cell histiocytosis of the juvenile xanthogranuloma family with characteristic bilateral symmetrical long bone osteosclerosis, associated with xanthogranulomatous extraskeletal organ involvement. In ECD, central nervous system (CNS) and orbital lesions are frequent, and more than half of ECD patients carry the V600E mutation of the proto-oncogene BRAF. The synchronous or metachronous development of ECD and Langerhans cell histiocytosis (LCH) in the same patients is rare, and the possible connection between them is still obscure. Cladribine is a purine substrate analogue that is toxic to lymphocytes and monocytes with good hematoencephalic penetration. Case report. We presented a 23-year-old man successfully treated with cladribine due to BRAF V600E-mutation-negative ECD with bilateral orbital and CNS involvement. ECD developed metachronously, 6 years after chemotherapy for multisystem LCH with complete disease remission and remaining central diabetes insipidus. During ECD treatment, the patient received 5 single-agent chemotherapy courses of cladribine (5 mg/m2 for 5 consecutive days every 4 weeks), with a reduction in dose to 4 mg/m2 in a fifth course, delayed due to severe neutropenia and thoracic dermatomal herpes zoster infection following the fourth course. Radiologic signs of systemic and CNS disease started to resolve 3 months after the end of chemotherapy, and CNS lesions completely resolved within 2 years after the treatment. After 12-year follow-up, there was no recurrence or appearance of new systemic or CNS xanthogranulomatous lesions or second malignancies. Conclusion. In accordance with our findings and recommendations provided by other authors, cladribine can be considered an effective alternative treatment for ECD, especially with CNS involvement and BRAF V600E-mutation-negative status, when interferon-α as the first-line therapy fails.
Keywords: erdheim-chester disease; histiocytosis; non-langerhans cells; orbital pseudotumor; central nervous system; brain stem; cerebellum; proto-oncogene proteins b-raf; cladribine; magnetic resonance imaging